Por qué llevamos uno - Suárez, Zuleyka (My University, 2022)
Utilizando solamente la casita de valores, se explica el concepto de suma y sus componentes exponiendo los casos que se pueden presentar y la explicación teórica de los mismos.

Using only the little house of values, the concept of addition and its components are explained, exposing the cases that can be presented and their theoretical explanation.
Keywords: Sumas; Matemáticas; Aritmética; Operaciones matemáticas; Sums; Mathematics; Arithmetic; Mathematical operations